Development of high-resolution two-dimensional correlation spectroscopy in solid-state NMR : applications to nanocomposites and fullerides - Lee, Daniel (2011)
Two-dimensional correlation spectroscopy in solid-state NMR is an immensely important tool for the analysis of materials, such as technologically interesting nano-materials or bio-materials. After detailing one method that returns high-resolution one-dimensional solid-state proton NMR spectra, high-resolution proton-proton two-dimensional correlation experiments are described and demonstrated. Subsequently, a new two-dimensional NMR experiment is described which is suitable for obtaining a high-resolution proton dimension in heteronuclear dipolar correlation spectra of solids. This new experiment has been used to characterise the interface between the organic and inorganic components of "coreshell" colloidal nanocomposite particles. In addition, a new two-dimensional NMR experiment is described which is suitable for obtaining homonuclear scalar correlation spectra in solids. This new experiment has several advantages, including increased cross peak intensities coupled with good suppression of the diagonal. Its utility is demonstrated via carbon-13 spectra of natural abundance samples as well as the polymer phase of caesium fulleride.